Revision of the spider crab genus Sargassocarcinus Ward, 1936 (Crustacea: Brachyura: Epialtidae) - Ng, Peter K. L.; Lin, Chia-Wei; Naruse, Tohru (Zootaxa, 2016)
The Western Pacific epialtid genus Sargassocarcinus Ward, 1936, is revised. The genus had been regarded as monotypic but is here shown to contain three species: S. sublimis (Rathbun, 1916), S. cristatus (Balss, 1924), and S. foliatus Ward, 1936 (type species). The many unusual characters possessed by Sargassocarcinus are figured and discussed; and diagnostic features of the three species are clarified. The taxonomy of the three species and aspects of their ecology are discussed. Sargassocarcinus species are found free-living on coral rubble habitats and not associated with macrophytic algae.